2011
DOI: 10.1166/jnn.2011.4985
|View full text |Cite
|
Sign up to set email alerts
|

Reduction of Graphene Oxide by Thiourea

Abstract: Various compounds with sulfur or diamine structure have been served as efficient reducing agents to convert graphene oxide to reduced graphene oxide. In this work, we used thiourea with both sulfur and diamine structure to synthesize reduced graphene oxide by the general wet chemical reduction method. The effective deoxygenation of graphene oxide was confirmed by Fourier transform infrared spectroscopy, X-ray photoelectron spectroscopy analysis and Raman spectroscopy. The as-prepared reduced graphene oxide is … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
35
1
2

Year Published

2013
2013
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 65 publications
(38 citation statements)
references
References 0 publications
0
35
1
2
Order By: Relevance
“…Furthermore, the diamine structure of thiourea can also help to reduce GO to graphene. [33] Our preliminary experiments showed that, among pristine Zn x Cd 1Àx S solid solutions with different stoichiometries prepared by using thiourea as the S source, the Zn 0.5 Cd 0.5 S solid solution exhibited the highest H 2 -production rate. Therefore, Zn 0.5 Cd 0.5 S solid solution was used in the following study.…”
Section: Introductionmentioning
confidence: 84%
See 1 more Smart Citation
“…Furthermore, the diamine structure of thiourea can also help to reduce GO to graphene. [33] Our preliminary experiments showed that, among pristine Zn x Cd 1Àx S solid solutions with different stoichiometries prepared by using thiourea as the S source, the Zn 0.5 Cd 0.5 S solid solution exhibited the highest H 2 -production rate. Therefore, Zn 0.5 Cd 0.5 S solid solution was used in the following study.…”
Section: Introductionmentioning
confidence: 84%
“…On the other hand, the amino groups in thiourea are activated by the C=S bonds, and thus thiourea molecules are grafted to the GO nanosheet through surface functional groups. [33] Thus, the metal cations (Zn 2+ and Cd 2 + ) and thiourea molecules tend to both be adsorbed on the surface of GO nanosheets through electrostatic attractions, and this leads to a predominantly heterogeneous nucleation process of ZCS NPs in the following reactions ( Figure 4). [38][39][40] Such in situ generation of ZCS NPs on graphene nanosheets facilitates close contact between the two phases, in agreement with Figure 2 a and b.…”
Section: Nucleation and Growth Mechanismmentioning
confidence: 99%
“…96,97 The most commonly used chemical reducing agents for the reduction of GO are hydrazine, [98][99][100][101] sodium borohydride, [102][103][104] Lawesson's reagent, 105 and thiourea. 106,107 Chemical reduction seems to be a very simple approach; however, it generates a graphene-like film containing low C:O ratio and a considerable quantity of residual functional groups, which leads to highly resistive film. [108][109][110] However, chemical reducing agents are toxic or explosive, resulting in challenges for large-scale production.…”
Section: Synthesis Of Graphenementioning
confidence: 99%
“…153 Ag-GO NPs may cause cell death by the following mechanisms: (i) GO could adhere to or wrap around E. coli through hydrogen bonds between the lipopolysaccharides of the bacteria and the oxygenated functional groups of GO. 107,152,155 (ii) GO could prevent uptake of nutrients from the surroundings while increasing the interaction between Ag NPs and the bacteria, 152 after which Ag NPs favor disruption of the bacterial membrane, leading to inhibition of respiration and replication of bacteria and eventually to cell death. 153,[155][156][157][158][159] (iii) The antibacterial effect of Ag-GO NPs could be caused by the "capturing-killing process", in which Ag-GO NPs contribute to the deposition of bacteria and increase the contact between the cells and the as-synthesized Ag NPs.…”
mentioning
confidence: 99%
“…Moreover the mechanism remains unclear. In view of this, the present investigation has been focussed on the use of thiourea as a reducing agent [16]. Compared to other reducing agents thiourea is less hazardous.…”
Section: Introductionmentioning
confidence: 99%